Gambaran Karakteristik Retinopati Diabetik pada Penderita Diabetes Melitus Tipe 2 - Syu’a Al Madina; Muhammad Jabal Nur; Hikmah Hiromi Razak Datu (Pusat riset dan Inovasi Nasional, 2025)
Diabetic retinopathy is a microvascular complication that often occurs in people with type 2 diabetes mellitus and is a major cause of blindness in older adults and the elderly. This study aims to describe the characteristics of diabetic retinopathy in people with type 2 diabetes mellitus through a literature review of 10 journals published between 2022 and 2025. The results of the analysis show that the prevalence of diabetic retinopathy globally reaches 35%, with the main risk factors including long duration of diabetes (>5 years), high HbA1c levels (>7%), and poor glycemic control. The majority of cases of diabetic retinopathy are found in the non-proliferative stage (65%), which is characterized by microaneurysms and retinal hemorrhages, while the proliferative stage is less common but has a high risk of causing blindness. The study also revealed that patients with comorbidities such as hypertension and dyslipidemia tend to experience more severe diabetic retinopathy. Further stages of diabetic retinopathy if not managed properly can cause vision-threatening conditions. However, low patient compliance in metabolic control and eye examination is a major challenge. Management of diabetic retinopathy requires a holistic approach that includes patient education, regular screening, and comprehensive risk factor control to prevent progression of diabetic retinopathy and maintain the quality of life of patients with type 2 diabetes mellitus.